Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
Through multi-stage doping and multi-metal element doping modification methods, lithium iron phosphate positive electrode active material with high uniformity carbon coating and excellent low-temperature performance was prepared, which solved the problems of poor low-temperature performance and high cost in the prior art, and achieved efficient battery performance improvement.
Patent Information
- Application Number
- CN202411752476.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-03-11
AI Technical Summary
Existing lithium iron phosphate batteries exhibit low energy density and low conductivity in low temperature environments, limiting their application range, and traditional small and small particle grading methods are costly and difficult to ensure mixing uniformity.
Using multi-stage doping positive electrode active material, three characteristic peaks appear through the particle size distribution curve of primary particles, and the method of co-doping modification of multi-metal elements is used to form vacancy and variable valence, broaden the diffusion channel of ions, and improve the mobility of lithium ions and electrons.
It realizes a high uniform carbon cladding layer, improves the conductivity and ion diffusion ability at low temperatures, combines high compaction density and excellent low temperature performance, and is simple in preparation, suitable for large-scale industrial production.
Smart Images

Figure CN119601654A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium iron phosphate materials have become the most widely used positive electrode materials in lithium-ion batteries due to their stable structure, good safety and long cycle life. However, with the development of society and technology, people have put forward higher requirements for energy storage devices including lithium-ion batteries. The problem of poor low-temperature performance has always been a bottleneck restricting its application in certain low-temperature environments. Therefore, improving the energy density and low-temperature performance of lithium iron phosphate batteries has become a hot topic in recent years. Grading of large and small particles is an effective method to increase the compaction density of powders. At present, it is known that lithium iron phosphate materials with different particle sizes are used for dry mixing and grading to prepare high-density lithium iron phosphate positive electrode materials. However, the above scheme adds the preparation of lithium iron phosphate precursors with different particle sizes, and the materials need to be dry mixed. The mixing uniformity cannot be guaranteed and the cost increases a lot. In fact, it is still impossible to obtain high-performance lithium iron phosphate positive electrode materials that take into account both low temperature and high performance. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a positive electrode active material and a preparation method thereof, a positive electrode plate, a battery and an electrical device, wherein the positive electrode active material can realize a graded structure, has a highly uniform carbon coating layer, has high conductivity and ion diffusion capacity at low temperatures, has both high compaction and good low temperature performance, and the preparation method of the positive electrode active material is simple and suitable for large-scale industrial production applications.
[0004] To this end, the present invention provides a positive electrode active material in a first aspect, including lithium iron phosphate, wherein the lithium iron phosphate is a secondary particle formed by agglomeration of primary particles, and the particle size number distribution curve of the primary particles presents three characteristic peaks;
[0005] Among them, the highest characteristic peak is the first characteristic peak, and the peak position D1 of the first characteristic peak is 100nm-300nm, and the corresponding number percentage N1 at the peak position D1 of the first characteristic peak is 25%-35%;
[0006] The second characteristic peak position D2 of the primary particles is 320nm-400nm, and the corresponding number percentage N2 at the second characteristic peak position D2 is 4%-9%;
[0007] The peak position D3 of the third characteristic peak of the primary particles is 450nm-620nm, and the corresponding number percentage N3 at the peak position D3 of the third characteristic peak is 0.5%-2%.
[0008] The positive electrode active material provided by the present invention is multi-stage blended, and the particle size number distribution curve of the primary particles presents three characteristic peaks, corresponding to the primary particles of the positive electrode active material being large and small particle gradations, indicating that the positive electrode active material contains nanometer-scale single crystal particles, which can gradually fill the gaps in large particles to obtain a high compaction density; at the same time, the method of co-doping and modification of multiple metal elements is adopted, which is conducive to the formation of vacancies and valence changes in the crystal structure of the positive electrode active material, broadens the diffusion channel of ions, and promotes the mobility of lithium ions and electrons in the material, thereby improving the conductivity and ion diffusion capacity at low temperatures, so that the secondary battery containing the positive electrode active material obtains better low-temperature performance.
[0009] According to an embodiment of the present invention, in the particle size distribution curve of the primary particles, there is a first minimum value D between the first characteristic peak and the second characteristic peak. 12 , the first minimum value D 12 The corresponding particle size range is 270nm-320nm, and the first minimum value D 12 The corresponding number percentage N 12 It is 3%-6%.
[0010] According to an embodiment of the present invention, the peak index γ of the positive electrode active material is 5%-40%;
[0011] Where γ=(N2-N 12 ) / N2×100%;
[0012] N 12 is the first minimum value D between the first characteristic peak and the second characteristic peak 12 The corresponding quantity percentage;
[0013] N2 is the quantity percentage corresponding to the peak position D2 of the second characteristic peak.
[0014] According to an embodiment of the present invention, in the particle size distribution curve of the primary particles, there is a second minimum value D between the second characteristic peak and the third characteristic peak. 23 , the second minimum value D 23 The corresponding particle size range is 400nm-500nm, and the second minimum value D 23 The corresponding number percentage N 23 It is 0.0%-0.5%.
[0015] According to an embodiment of the present invention, the D 50 0.1μm-1.0μm.
[0016] According to an embodiment of the present invention, the D 50 0.7μm-2.0μm.
[0017] According to an embodiment of the present invention, the compaction density of the positive electrode active material is 2.45 g / cm 3 -2.65g / cm 3 .
[0018] According to an embodiment of the present invention, the specific surface area of the positive electrode active material is 10 m 2 / g-13m 2 / g.
[0019] According to an embodiment of the present invention, the positive electrode active material includes a substrate and a carbon coating layer coated on the surface of the substrate;
[0020] Wherein, the matrix has a composition shown in Formula I:
[0021] Li 1+a Fe b M c (PO4) d Formula I;
[0022] Among them, -0.1≤a≤0.1, 0≤b≤1, 0≤c≤0.5, 0≤d≤1;
[0023] M is selected from at least one of La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al.
[0024] According to an embodiment of the present invention, M is Nb, and at least one of Al, Nb, W, Co, V and Ti.
[0025] According to an embodiment of the present invention, based on the total weight of the positive electrode active material, the content of the carbon coating layer is 0.5 wt %-2 wt %, preferably 1 wt %-1.5 wt %.
[0026] The second aspect of the present invention provides a method for preparing the positive electrode active material according to the first aspect, the preparation method comprising:
[0027] A first mixed solution containing a first iron phosphate, a first lithium source, a first carbon source, and a first M source is prepared, and a first slurry is obtained by grinding, and a first precursor is obtained by a first spray drying process;
[0028] A second mixed solution containing a second iron phosphate, a second lithium source, a second carbon source, and a second M source is prepared, and a second slurry is obtained by grinding, and a second precursor is obtained by a second spray drying process;
[0029] Mixing the first precursor and the second precursor, and sintering to obtain the positive electrode active material;
[0030] The D of the first slurry50 Less than the D of the second slurry 50 .
[0031] The present invention prepares slurries of different particle sizes, obtains precursors of different particle sizes and mixes them, realizes mixed gradation of large and small particles in the precursor stage, and then undergoes sintering and crystallization, the particle size increases with the level of the primary particles, greatly optimizes the particle gradation of the material, and makes the particles more tightly bonded, thereby preparing a positive electrode active material with both high capacity and high compaction density performance. At the same time, the preparation method has a simple process flow and low equipment requirements, and is suitable for application in large-scale industrial production.
[0032] According to an embodiment of the present invention, D 50 With the second slurry D 50 The difference is greater than 0.2μm.
[0033] According to an embodiment of the present invention, the particle size of the first iron phosphate is 80nm-200nm; the particle size of the second iron phosphate is 50nm-160nm.
[0034] According to an embodiment of the present invention, the particle size D of the first precursor 50 smaller than the particle size D of the second precursor 50 .
[0035] According to an embodiment of the present invention, the specific surface area of the first iron phosphate is 8m 2 / g-14m 2 / g.
[0036] According to an embodiment of the present invention, the specific surface area of the second iron phosphate is 6m 2 / g-10m 2 / g.
[0037] According to an embodiment of the present invention, the first iron phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.960-0.980.
[0038] According to an embodiment of the present invention, the second ferric phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.950-0.970.
[0039] According to an embodiment of the present invention, the first lithium source and the second lithium source are independently selected from one of lithium hydroxide, lithium carbonate and lithium acetate.
[0040] According to an embodiment of the present invention, the lithium iron molar ratio Li / Fe of the first lithium source and the first iron phosphate is 1.01-1.07.
[0041] According to an embodiment of the present invention, the lithium iron molar ratio Li / Fe of the second lithium source and the second iron phosphate is 1.01-1.07.
[0042] According to an embodiment of the present invention, the first carbon source is selected from at least one of glucose, sucrose, starch, polyethylene glycol, and citric acid.
[0043] According to an embodiment of the present invention, the amount of the first carbon source added satisfies that the mass ratio of carbon to the mass ratio of the positive electrode active material is 1.0 wt%-1.8 wt%.
[0044] According to an embodiment of the present invention, the second carbon source is selected from at least one of glucose, sucrose, polyethylene glycol, and citric acid.
[0045] According to an embodiment of the present invention, the amount of the second carbon source added satisfies that the mass ratio of carbon to the mass ratio of the positive electrode active material is 1.0wt%-1.4wt%.
[0046] According to an embodiment of the present invention, the solid content of the first slurry is 35wt%-50wt%.
[0047] According to an embodiment of the present invention, the solid content of the second slurry is 35wt%-50wt%.
[0048] According to an embodiment of the present invention, D 50 0.25μm-0.45μm.
[0049] According to an embodiment of the present invention, D 50 It is 0.45μm-0.80μm.
[0050] According to an embodiment of the present invention, the air inlet temperature of the first spray drying process and the second spray drying process is independently 200°C-260°C, and the air outlet temperature is independently 80°C-110°C.
[0051] According to an embodiment of the present invention, the rotation speed of the atomizer in the first spray drying process and the second spray drying process is independently 30-50 Hz.
[0052] According to an embodiment of the present invention, the particle size D of the first precursor and the second precursor is 50 Independently 15 μm-45 μm, water content ≤3.0%.
[0053] According to an embodiment of the present invention, the first precursor and the second precursor are mixed in a mass ratio of (3:7)-(7:3).
[0054] According to an embodiment of the present invention, the sintering temperature is 750° C.-850° C., and the sintering time is 6 h-12 h.
[0055] The third aspect of the present invention provides a positive electrode plate, the positive electrode plate comprising the positive electrode active material described in the first aspect or the positive electrode active material prepared by the preparation method described in the second aspect. Thus, the plate has a high compaction density and exhibits high capacity, high rate, and excellent low temperature performance in electrochemical work.
[0056] The fourth aspect of the present invention provides a battery, the battery comprising the positive electrode sheet of the third aspect, so that the battery has good electrochemical performance.
[0057] A fifth aspect of the present invention provides an electrical device, wherein the electrical device comprises the battery described in the fourth aspect.
[0058] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0060] Figure 1 The SEM image of the lithium iron phosphate positive electrode active material prepared in Example 1 of the present invention is shown;
[0061] Figure 2 The XRD pattern of the lithium iron phosphate positive electrode active material prepared in Example 1 of the present invention is shown;
[0062] Figure 3 The particle size distribution curve of the primary particles of the lithium iron phosphate positive electrode active material prepared in Example 1 of the present invention is shown;
[0063] Figure 4 The particle size distribution curve of the primary particles of the lithium iron phosphate positive electrode active material prepared in Comparative Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0064] The following embodiments of the technical solution of the present invention are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0065] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0066] "Scope" disclosed in the present invention is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0067] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0068] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0069] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0070] A first aspect of the present invention provides a positive electrode active material, wherein the positive electrode active material is a secondary particle formed by agglomeration of primary particles, and a particle size number distribution curve of the primary particles presents three characteristic peaks;
[0071] Among them, the highest characteristic peak is the first characteristic peak, and the peak position D1 of the first characteristic peak is 100nm-300nm, and the corresponding number percentage N1 at the peak position D1 of the first characteristic peak is 25%-35%;
[0072] The second characteristic peak position D2 of the primary particles is 320nm-400nm, and the corresponding number percentage N2 at the second characteristic peak position D2 is 4%-9%;
[0073] The peak position D3 of the third characteristic peak of the primary particles is 450nm-620nm, and the corresponding number percentage N3 at the peak position D3 of the third characteristic peak is 0.5%-2%.
[0074] The particle size distribution curve of the primary particles of the positive electrode active material provided by the present invention presents three characteristic peaks, indicating that the positive electrode active material contains primary particles of at least three particle size distributions, indicating that the positive electrode active material contains single crystal particles of nanometer scale of different sizes, which can be filled in the gaps of large particles to significantly improve the overall compaction density of the powder. At the same time, the method of co-doping and modification of multiple metal elements is used, which is conducive to the formation of vacancies and valence changes in the crystal structure of the positive electrode active material, broadening the diffusion channel of ions, and promoting the mobility of lithium ions and electrons in the material, thereby improving the conductivity and ion diffusion capacity at low temperatures, so that the secondary battery containing the positive electrode active material obtains better low temperature performance.
[0075] The particle size distribution curve is obtained by plotting the particle size of the primary particles as the abscissa and the percentage of the sum of the number of particles having the particle size in the total number of all particles as the ordinate.
[0076] According to a specific embodiment of the present invention, the second characteristic peak position D2 of the primary particle is 320nm-400nm, and the corresponding number percentage N2 at the second characteristic peak position D2 is 4%-9%. This shows that the primary particle has small particles in this particle size range, which can further effectively fill the gaps in large particles, so that the positive electrode active material obtains a high compaction density. When the particle size is too large, the ion migration path will be too long, reducing the capacity and charge and discharge efficiency; if the particle size is too small, it will affect the cycle life of the material. Therefore, when the second characteristic peak is 320nm-400nm, the capacity of the particle itself, the balance of the cycle and the better low-temperature performance can be taken into account.
[0077] According to a specific embodiment of the present invention, there is a first minimum value D between the first characteristic peak and the second characteristic peak. 12 , the first minimum value D 12 The corresponding particle size range is 270nm-320nm, and the first minimum value D 12 The corresponding number percentage N 12 The first characteristic peak and the second characteristic peak thus have a more obvious peak separation effect.
[0078] According to a specific embodiment of the present invention, the peak index γ of the positive electrode active material is 5%-40%;
[0079] Where γ=(N2-N 12 ) / N2×100%;
[0080] N 12 is the first minimum value D between the first characteristic peak and the second characteristic peak 12 The corresponding quantity percentage;
[0081] N2 is the quantity percentage corresponding to the peak position D2 of the second characteristic peak.
[0082] When the particle size distribution of the first characteristic peak and / or the second characteristic peak is relatively wide, although the first characteristic peak and the second characteristic peak appear in the particle size distribution curve after mixing, the peak separation effect is not obvious, which is manifested as the volume percentage of the minimum value between the first characteristic peak and the second characteristic peak is relatively close to the maximum value of the second characteristic peak, and the compaction density improvement effect of the particles is still small. Therefore, when the peak separation index γ meets the definition of the present invention, on the one hand, large and small particles can be effectively distributed in the structure to form a filling effect, so that the positive electrode active material obtains a higher compaction density; on the other hand, too large particles cannot be mixed, so that the large particles can maintain good capacity and cycle performance.
[0083] According to a specific embodiment of the present invention, the third characteristic peak position D3 of the primary particles is 450nm-620nm, and the corresponding number percentage N3 at the third characteristic peak position D3 is 0.5%-2%. This further improves the compaction density, realizes that the positive electrode active material is composed of small particles and large particles of a specific particle size, and achieves the densest stacking, thereby improving the compaction density of the manufactured pole piece.
[0084] According to a specific embodiment of the present invention, in the particle size distribution curve of the primary particles, there is a second minimum value D between the second characteristic peak and the third characteristic peak. 23 , the second minimum value D 23 The corresponding particle size range is 400nm-500nm, and the second minimum value D 23 The corresponding number percentage N 23 It is 0.0%-0.5%.
[0085] According to a specific embodiment of the present invention, the D 50 As some specific examples, the D 50 It is 0.1μm, 0.5μm, 1.0μm, etc.
[0086] According to a specific embodiment of the present invention, the D 50 As some specific examples, the secondary particles have a D 500.7μm, 1μm, 1.5μm, 1.8μm, 2.0μm, etc.
[0087] According to a specific embodiment of the present invention, the compaction density of the positive electrode active material is 2.45 g / cm 3 -2.65g / cm 3 As some specific examples, the compaction density of the positive electrode active material is 2.45 g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.65g / cm 3 wait.
[0088] According to a specific embodiment of the present invention, the specific surface area of the positive electrode active material is 10m 2 / g-13m 2 As some specific examples, the specific surface area of the positive electrode active material is 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, etc.
[0089] According to a specific embodiment of the present invention, the positive electrode active material includes a substrate and a carbon coating layer coated on the surface of the substrate;
[0090] Wherein, the matrix has a composition shown in Formula I:
[0091] Li 1+a Fe b M c (PO4) d Formula I;
[0092] Among them, -0.1≤a≤0.1, 0≤b≤1, 0≤c≤0.5, 0≤d≤1;
[0093] M is at least one selected from La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al;
[0094] Preferably, M is selected from Nb and further includes at least one of Al, Nb, W, Co, V and Ti.
[0095] According to a specific embodiment of the present invention, based on the total weight of the positive electrode active material, the content of the carbon coating layer is 0.5wt%-2wt%. As some specific examples, the content of the carbon coating layer is 0.5wt%, 1wt%, 1.5wt%, 2wt%, etc., preferably 1wt%-1.5wt%.
[0096] The second aspect of the present invention provides a method for preparing the above-mentioned positive electrode active material, the preparation method comprising:
[0097] (1) preparing a first mixed solution containing a first iron phosphate, a first lithium source, a first carbon source, and a first M source, performing a first grinding to obtain a first slurry, and performing a first spray drying process to obtain a first precursor.
[0098] According to a specific embodiment of the present invention, the particle size of the first iron phosphate is 80nm-200nm. As some specific examples, the particle size of the first iron phosphate may be 80nm, 100nm, 150nm, 200nm, etc.
[0099] According to a specific embodiment of the present invention, the specific surface area of the first iron phosphate is 8m 2 / g-14m 2 / g, as some specific examples, the specific surface area of the first iron phosphate may be 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, etc. Further, the first ferric phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.960-0.980, such as 0.960, 0.970, 0.980, etc.
[0100] According to a specific embodiment of the present invention, the specific type of the first lithium source is not particularly limited, and those skilled in the art may select it according to actual conditions. For example, the first lithium source may include at least one of lithium hydroxide, lithium carbonate, and lithium acetate, preferably lithium carbonate, and more preferably lithium carbonate with a purity of ≥99.5%.
[0101] According to a specific embodiment of the present invention, the lithium iron molar ratio Li / Fe of the first lithium source and the first iron phosphate is 1.01-1.07, for example, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, etc.
[0102] According to a specific embodiment of the present invention, the specific type of the first carbon source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the first carbon source can include at least one of glucose, sucrose, starch, polyethylene glycol, and citric acid. Further, the amount of the first carbon source added satisfies that the carbon mass accounts for 1.0wt%-1.8wt% of the mass ratio of the positive electrode active material, such as 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, etc.
[0103] According to a specific embodiment of the present invention, the specific type of the first M source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the first M source may include at least one of the salts, hydroxides, and oxides that can provide at least one element among La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al, preferably aluminum oxide, titanium dioxide, ammonium metavanadate, tungsten trioxide, magnesium oxide, cobalt oxyhydroxide, and niobium pentoxide, wherein the addition amounts of titanium dioxide, ammonium metavanadate, tungsten trioxide, and niobium pentoxide meet the titanium, vanadium, tungsten, and niobium contents of the target positive electrode active material of 1000ppm-5000ppm, 1000ppm-2000ppm, 500ppm-2000ppm, and 500-2000ppm, respectively.
[0104] According to a specific embodiment of the present invention, the preparation method of the first mixed solution is not particularly limited, and it does not affect subsequent grinding, spray drying and other steps. Specifically, the first mixed solution can be obtained by dissolving the first iron phosphate, the first lithium source, the first carbon source, and the first M source in a solvent, and the solvent includes but is not limited to deionized water.
[0105] According to a specific embodiment of the present invention, the solid content of the first slurry is 35wt%-50wt%, and the grinding is performed so that the particle size D of the first slurry is 50 The grinding method is not particularly limited and can be selected according to the actual situation in the art, as long as the particle size of the slurry is within the target range, such as by sand grinding.
[0106] According to a specific embodiment of the present invention, the air inlet temperature and air outlet temperature of the first spray drying process are not particularly limited, that is, the slurry can be dried, and the water content of the spray-dried product (i.e., the first precursor) is preferably ≤3.0%. As some specific examples, the air inlet temperature of the first spray drying process can be 200°C-260°C, and the air outlet temperature can be 80°C-110°C. At the same time, the atomizer speed of the second spray drying process can be 30-50Hz.
[0107] According to a specific embodiment of the present invention, the particle size D of the first precursor 50 Smaller than the particle size D of the second precursor 50 As some specific examples, the particle sizes D of the first precursor and the second precursor are 50 The particle size can be independently 15 μm to 45 μm. This particle size can be achieved by pulverizing after spray drying.
[0108] (2) preparing a second mixed solution containing a second iron phosphate, a second lithium source, a second carbon source, and a second M source, grinding the mixed solution to obtain a second slurry, and performing a second spray drying process to obtain a second precursor.
[0109] According to a specific embodiment of the present invention, the particle size of the second iron phosphate is 50nm-160nm. As some specific examples, the particle size of the first iron phosphate may be 50nm, 70nm, 100nm, 130nm, 160nm, etc.
[0110] According to a specific embodiment of the present invention, the specific surface area of the second iron phosphate is 6m 2 / g-10m 2 / g, as some specific examples, the specific surface area of the second iron phosphate may be 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, etc. Further, the second ferric phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.950-0.970, such as 0.950, 0.960, 0.970, etc.
[0111] According to a specific embodiment of the present invention, the specific type of the second lithium source is not particularly limited, and those skilled in the art may select it according to actual conditions. For example, the second lithium source may include at least one of lithium hydroxide, lithium carbonate, and lithium acetate, preferably lithium carbonate, and more preferably lithium carbonate with a purity of ≥99.5%.
[0112] According to a specific embodiment of the present invention, the lithium iron molar ratio Li / Fe of the second lithium source and the second iron phosphate is 1.01-1.07, for example, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, etc.
[0113] According to a specific embodiment of the present invention, the specific type of the second carbon source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the second carbon source can include at least one of glucose, sucrose, polyethylene glycol, and citric acid. Further, the amount of the second carbon source added satisfies that the carbon mass accounts for 1.0wt%-1.4wt% of the mass ratio of the positive electrode active material, such as 1.0wt%, 1.2wt%, 1.4wt%, etc.
[0114] According to a specific embodiment of the present invention, the specific type of the second M source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the second M source may include at least one of the salts, hydroxides, and oxides that can provide at least one element among La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al, preferably aluminum oxide, titanium dioxide, ammonium metavanadate, tungsten trioxide, magnesium oxide, cobalt oxyhydroxide, and niobium pentoxide, wherein the addition amounts of titanium dioxide, ammonium metavanadate, and tungsten trioxide meet the titanium, vanadium, and tungsten contents of the target positive electrode active material of 1000ppm-5000ppm, 1000ppm-2000ppm, and 500ppm-2000ppm, respectively.
[0115] According to a specific embodiment of the present invention, the preparation method of the second mixed solution is not particularly limited, and it does not affect subsequent grinding, spray drying and other steps. Specifically, the second mixed solution can be obtained by dissolving the second iron phosphate, the second lithium source, the second carbon source, and the second M source in a solvent, and the solvent includes but is not limited to deionized water.
[0116] According to a specific embodiment of the present invention, D 50 Less than the D of the second slurry 50 ; Preferably the first slurry D 50 With the second slurry D 50 The difference is greater than 0.2μm. By preparing slurries with different particle sizes, precursors with different particle sizes are obtained and blended, and mixed gradation of large and small particles is achieved in the precursor stage. After subsequent sintering and crystallization, the particle size increases with the level of the primary particles, which greatly optimizes the particle gradation of the material, and the particles are more tightly bound, which is conducive to the preparation of positive electrode active materials with both high capacity and high compaction density performance. 50 The difference is greater than 0.2μm, achieving better mixing effect.
[0117] According to a specific embodiment of the present invention, the solid content of the second slurry is 35wt%-50wt%, and the grinding is performed so that the particle size D of the second slurry is 50 The grinding method is not particularly limited and can be selected according to the actual situation in the art, as long as the particle size of the slurry is within the target range, such as by sand grinding.
[0118] According to a specific embodiment of the present invention, the air inlet temperature and air outlet temperature of the second spray drying process are not particularly limited, that is, the slurry can be dried, and the water content of the spray-dried product (i.e., the second precursor) is preferably ≤3.0%. As some specific examples, the air inlet temperature of the second spray drying process can be 200°C-260°C, and the air outlet temperature can be 80°C-110°C. At the same time, the atomizer speed of the second spray drying process can be 30-50Hz.
[0119] (3) The first precursor and the second precursor are mixed and sintered to obtain the positive electrode active material.
[0120] According to a specific embodiment of the present invention, the mixing ratio of the first precursor and the second precursor is not particularly limited, and those skilled in the art can make reasonable adjustments according to the circumstances. As some specific examples, the first precursor and the second precursor are mixed in a mass ratio of (3:7)-(7:3), such as 3:7, 2:3, 1:1, 3:2, 7:3, etc.
[0121] According to a specific embodiment of the present invention, the sintering temperature and time are not particularly limited, and those skilled in the art can reasonably adjust them according to the situation. As some specific examples, the sintering temperature can be 750°C-850°C, and the sintering time can be 6h-12h. Furthermore, the sintering is preferably carried out in an inert atmosphere, such as nitrogen.
[0122] The third aspect of the present invention provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0123] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0124] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0125] The positive electrode active material includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0126] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present invention does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0127] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.
[0128] These materials are all commercially available.
[0129] The fourth aspect of the present invention provides a battery, which comprises the positive electrode sheet according to the third aspect of the present invention, so that the battery has an excellent cycle life.
[0130] A battery is a battery that can be used again by recharging the active materials after discharge.
[0131] It is understandable that the battery proposed in the present invention is a lithium-ion battery.
[0132] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0133] [Negative electrode]
[0134] In the battery, the negative electrode plate may be lithium metal or a lithium-containing alloy.
[0135] In some embodiments, in order to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.
[0136] The negative electrode active material layer may also optionally include a binder, a conductive agent and other optional auxiliary agents.
[0137] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0138] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0139] As examples, other optional additives may include thickening and dispersing agents (eg, sodium carboxymethylcellulose CMC-Na), and PTC thermistor materials.
[0140] [Electrolyte]
[0141] The electrolyte may include an electrolyte salt and a solvent.
[0142] As an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0143] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0144] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0145] [Isolation film]
[0146] As the above-mentioned isolation membrane, the present invention has no particular limitation and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs, for example, it can include a combination of at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0147] The fifth aspect of the present invention provides an electric device, which includes the battery described in the fourth aspect. Specifically, the battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can include but is not limited to mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.
[0148] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0149] The relevant parameters in the following examples and comparative examples were obtained by testing using the following methods:
[0150] (1) Morphology test: obtained by scanning electron microscope Regulus 8100 of Hitachi, Japan;
[0151] (2) X-ray diffraction (XRD) test: obtained by SmartLab 9kW X-ray diffractometer of Rigaku Corporation;
[0152] (3) Median particle size D 50 : Measured by Marvern's Mastersizer 3000 laser particle size analyzer;
[0153] (4) Average primary particle size: A scanning electron microscope image of the prepared lithium iron phosphate positive electrode active material was taken at a magnification of 30.0K, and the average primary particle size was calculated using LIBMAS and Nano Measurer software;
[0154] (5) Specific surface area (BET) test: obtained by using Micromeritics' Tristar 3020 surface area analyzer;
[0155] (6) Powder compaction density test: Weigh 1g of the prepared lithium iron phosphate positive electrode active material and put it into a compaction mold. Put the mold into a compaction device to test the result under a pressure of 30KN;
[0156] (7) Particle size distribution test: The prepared lithium iron phosphate positive electrode active material was photographed at 30.0K magnification using a scanning electron microscope, and statistical data was obtained using LIBMAS analysis software;
[0157] (8) Electrochemical performance test: A button half-cell was used for testing, with a test voltage of 2.5V-4.2V. The battery was charged to 4.2V using a constant current and constant voltage charging method, and discharged to 2.5V using a constant current and discharge method. The charge and discharge current was 0.1C for 2 cycles; then 0.2C for 1 cycle; then 0.33C for 1 cycle; then 0.5C for 1 cycle; then 1C for 1 cycle; then 2C for 1 cycle, with the cut-off voltage condition being the same as 0.1C.
[0158] Example 1
[0159]
Preparation of lithium iron phosphate positive electrode active material
[0160] (1) 5005.0 g of iron phosphate having a Fe / P molar ratio of 0.970 and a particle size of 110 nm was mixed with 1235.10 g of lithium carbonate, 420 g of glucose, 150 g of polyethylene glycol, 16.32 g of titanium dioxide, 12.10 g of ammonium metavanadate, 4.68 g of niobium pentoxide and 11250 g of pure water were added and mixed in a stirred mill to form a first mixed solution; the first mixed solution was put into a sand mill and sanded at a temperature below 45° C., and the sanded particle size D was controlled. 50 The particle size is 0.30 μm and the solid content is 38 wt % to obtain a first slurry;
[0161] The first slurry was spray dried, and the air inlet temperature was controlled at 250°C, the air outlet temperature was 100°C, and the atomizer speed was 50 Hz to obtain a particle size D 50 A first precursor having a particle size of 15 μm and a water content of ≤3.0%;
[0162] (2) 4009.0 g of iron phosphate with a Fe / P molar ratio of 0.960 and a particle size of 150 nm and 985.0 g of lithium carbonate were mixed, 305 g of glucose, 120 g of polyethylene glycol, 8.20 g of titanium dioxide and 8830 g of pure water were added and mixed in a stirred mill to form a second mixed solution; the second mixed solution was put into a sand mill and sanded at a temperature below 45° C., and the sanding particle size D was controlled. 50 The particle size was 0.70 μm and the solid content was 38 wt % to obtain a second slurry;
[0163] The second slurry was spray dried, the feed inlet temperature was controlled at 250°C, the discharge port temperature was controlled at 100°C, the atomizer speed was controlled at 34 Hz, and a particle size of D was obtained. 50 A second precursor having a particle size of 40 μm and a water content of ≤3.0%;
[0164] (3) The first precursor and the second precursor were mixed in a high-speed mixer at a mass ratio of 7:3, and then calcined at high temperature under a nitrogen atmosphere, with the sintering temperature controlled at 790°C and the sintering time controlled at 10 h; then crushed to control the particle size D 50 The particle size of the primary particles is 1.4 μm, and the average primary particle size is 172 nm, thereby obtaining a high compaction density lithium iron phosphate positive electrode active material.
[0165]
Preparation of positive electrode
[0166] The lithium iron phosphate positive electrode active material prepared above, 50% Compressed Denka Black (acetylene black, compression ratio of 50%), and polyvinylidene fluoride (PVDF) are dispersed in N-methylpyrrolidone (NMP) in a mass ratio of 96.5:1.5:2, and after being evenly dispersed by ball milling, they are coated on aluminum foil and vacuum dried to obtain a positive electrode sheet.
[0167]
Preparation of negative electrode sheet
[0168] The negative electrode uses a Li metal sheet.
[0169]
Preparation of electrolyte
[0170] A 1.1 mol / L LiPF6 solution was used as the electrolyte, with an equal volume mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) as the solvent.
[0171]
Isolation film
[0172] Celgard polypropylene film was used as the isolation membrane.
[0173] The positive electrode sheet, the separator, the negative electrode sheet and the electrolyte are assembled into a button-type half-cell.
[0174] The lithium ion batteries containing positive electrode active materials of Examples 2-6 and Comparative Example 1 are substantially the same as Example 1 except for some different parameters (see Table 1). The type and amount of the M element are adjusted to make the compound have the composition shown in Table 3.
[0175] In Example 4, “titanium dioxide, ammonium metavanadate, niobium pentoxide” in step (1) of Example 1 is replaced by “titanium dioxide, Y-containing compound, Mg-containing compound”; and in Example 6, “titanium dioxide, ammonium metavanadate, niobium pentoxide” in step (1) of Example 1 is replaced by “titanium dioxide, Zr-containing compound, Sb-containing compound”.
[0176] Comparative Example 1 Compared with Example 1, the atomizer speed of the first spray drying and the second spray drying, the D of the first precursor and the second precursor were adjusted. 50 Size, D of the second slurry50 size.
[0177] The scheme of comparative example 2 is specifically as follows:
[0178] (1) 2785.0 g of Fe / P with a molar ratio of 0.970 and a specific surface area of 10.0 m 2 / g and iron phosphate with a particle size of 110nm, 1195.0g Fe / P molar ratio of 0.960, and a specific surface area of 8.0m 2 / g and iron phosphate with a particle size of 150nm and 984.30g of lithium carbonate are mixed, 310g of glucose, 120g of polyethylene glycol, 16.80g of titanium dioxide, 13.50g of ammonium metavanadate and 8870g of pure water are added and mixed in a stirred mill to form a first mixed solution; the first mixed solution is put into a sand mill and sanded at below 45°C to control the sanding particle size D 50 The particle size was 0.42 μm and the solid content was 38 wt % to obtain a first slurry;
[0179] The first slurry was spray-dried, the feed inlet temperature was controlled to be 245° C., the discharge outlet temperature was controlled to be 95° C., and the atomizer speed was controlled to be 35 Hz, to obtain a first precursor having a particle size D50 of 25 μm and a moisture content of ≤3.0%;
[0180] (2) The first precursor powder is calcined at high temperature in a nitrogen atmosphere, the sintering temperature is controlled to be 790°C, and the sintering time is 10 h; then it is crushed to control the particle size D 50 The particle size of the primary particles is 1.6 μm, and the average primary particle size is 200 nm, thereby obtaining a lithium iron phosphate positive electrode material.
[0181] The difference between Comparative Example 3 and Comparative Example 2 is that the D of the first slurry and the first precursor is adjusted. 50 size.
[0182] The primary particle size distribution data of the positive electrode active materials obtained in Examples 1-6 and Comparative Examples 1-3 are shown in Table 2, and the performance parameters of the positive electrode active materials are shown in Table 3.
[0183] Compared with Example 1, Example 2 is different in that the mixing ratio of the first slurry and the second slurry is adjusted; compared with Example 1, Example 3 is different in that the particle size of the second iron phosphate and the D 50 size, and the atomizer speed of the second spray drying; the difference between Example 4 and Example 1 is that the selection of M source is adjusted (from V, Nb to Y, Mg); the difference between Example 5 and Example 1 is that the particle size of the first iron phosphate, the D of the first slurry and the second slurry are adjusted 50 size, the atomizer speed of the first spray drying and the second spray drying, the D50 Compared with Example 1, Example 6 differs in that the D of the second precursor is adjusted. 50 Size, and adjusted the selection of M source (from V, Nb to Zr, Sb);
[0184] Comparative Example 1 is compared with Example 1 in that the atomizer speed of the first spray drying and the second spray drying, the D of the first precursor and the second precursor are adjusted. 50 Size, D of the second slurry 50 Compared with Example 1, Comparative Example 2 is different in that the first slurry and the second slurry are not prepared separately, but the mixed solution containing the first iron phosphate and the mixed solution containing the second iron phosphate are mixed at the same time, and then ground, dried and calcined, and the raw material does not contain niobium pentoxide; Comparative Example 3 is based on Comparative Example 2, and the D of the first slurry and the first precursor is adjusted. 50 size.
[0185] Table 1
[0186]
[0187]
[0188] In Table 1, “ / ” means no addition or none.
[0189] Table 2
[0190]
[0191]
[0192] In Table 1, “ / ” means none.
[0193] Table 3
[0194]
[0195]
[0196] Result analysis:
[0197] Compared with Comparative Examples 1-3, the positive electrode active materials prepared by the method provided by the present invention (ie, Examples 1-6) have higher compaction density, higher capacity, higher rate, and better low-temperature performance.
[0198] in, Figure 1 This is a SEM image of the lithium iron phosphate positive electrode active material prepared in Example 1, from which it can be seen that mixed particles of various different particle sizes are blended. Figure 2 This is the XRD diagram corresponding to the material, and it can be seen that it has a lithium iron phosphate structure. Figure 3This is the particle size distribution curve of the primary particles of the material. It can be seen that it has three obvious characteristic peaks.
[0199] Similarly, the remaining embodiments have the same excellent effects. Compared with Embodiment 1, Embodiment 3 adjusts the particle size of the second iron phosphate and the D 50 size, so that the first slurry and the second slurry D 50 The difference is small (0.15 μm), compared with the D 50 For Examples 1-2 and 4, which have a larger difference, the grading effect is reduced, but still better than Comparative Examples 1-3, indicating that the D 50 A difference greater than 0.2 μm is more conducive to achieving high compaction density and better electrochemical performance.
[0200] Compared with Example 1, Example 4 changes the selection of M element (from V and Nb to Y and Mg), and the results show that the compaction density of the positive electrode active material is reduced, and the capacity and low-temperature capacity retention rate of the battery containing the positive electrode active material are reduced, but still better than Comparative Examples 1-3, indicating that the selection of M source is preferably V or Nb source. Compared with Example 1, Example 6 changes the selection of M element (from V and Nb to Zr and Sb), and the results show that the compaction density of the positive electrode active material is reduced, and the capacity and low-temperature capacity retention rate of the battery containing the positive electrode active material are reduced, but still better than Comparative Examples 1-3, also indicating that the selection of M source is preferably V or Nb source.
[0201] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that the atomizer speed of the first spray drying and the second spray drying, the D of the first precursor and the second precursor are adjusted. 50 Size, D of the second slurry 50 Size. The D of the first slurry and the second slurry in this comparative example 50 The same, simultaneously prepared precursor D 50 The same is true, that is, although the preparation method uses iron phosphate with different particle sizes, the D of the slurry is not controlled. 50 range, resulting in the material not being able to achieve multi-stage blending, so the compaction density of the prepared positive electrode active material is reduced, and the capacity and low-temperature capacity retention rate of the battery containing it are reduced.
[0202] Compared with Example 1, Comparative Example 2 is different in that two materials with different particle sizes are directly mixed, then ground, dried and calcined. Therefore, the preparation method does not achieve mixed gradation of large and small particles in the slurry stage, and only one type of precursor is obtained. This disadvantage is further magnified in the subsequent calcination process. Figure 4It can be seen that the particle size number distribution curve of the primary particles of the material has only one obvious characteristic peak, which also proves that the material has not achieved multi-stage blending, resulting in a decrease in the compaction density of the prepared positive electrode active material, and a decrease in the capacity and low-temperature capacity retention rate of the battery containing it.
[0203] Comparative Example 3 is similar to the preparation method of Comparative Example 2, except that the D of the first slurry and the first precursor is adjusted. 50 The results show that the material does not achieve multi-stage blending, resulting in a decrease in the compaction density of the prepared positive electrode active material, and a decrease in the capacity of the battery containing it and the low-temperature capacity retention rate.
[0204] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0205] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: The lithium iron phosphate is a secondary particle formed by agglomeration of primary particles, and a particle size distribution curve of the primary particles presents three characteristic peaks; Among them, the highest characteristic peak is the first characteristic peak, and the peak position D1 of the first characteristic peak is 100nm-300nm, and the corresponding number percentage N1 at the peak position D1 of the first characteristic peak is 25%-35%; The second characteristic peak position D2 of the primary particles is 320nm-400nm, and the corresponding number percentage N2 at the second characteristic peak position D2 is 4%-9%; The peak position D3 of the third characteristic peak of the primary particles is 450nm-620nm, and the corresponding number percentage N3 at the peak position D3 of the third characteristic peak is 0.5%-2%.
2. The positive electrode active material according to claim 1, characterized in that In the particle size distribution curve of the primary particles, there is a first minimum value D between the first characteristic peak and the second characteristic peak. 12 , the first minimum value D 12 The corresponding particle size range is 270nm-320nm, and the first minimum value D 12 The corresponding number percentage N 12 3%-6%; Optionally, the peak index γ of the positive electrode active material is 5%-40%; Where γ=(N2-N 12 ) / N2×100%; N 12 is the first minimum value D between the first characteristic peak and the second characteristic peak 12 The corresponding quantity percentage; N2 is the quantity percentage corresponding to the peak position D2 of the second characteristic peak.
3. The positive electrode active material according to claim 1 or 2, characterized in that: In the particle size distribution curve of the primary particles, there is a second minimum value D between the second characteristic peak and the third characteristic peak. 23 , the second minimum value D 23 The corresponding particle size range is 400nm-500nm, and the second minimum value D 23 The corresponding number percentage N 23 It is 0.0%-0.5%.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The D of the primary particles 50 0.1μm-1.0μm; Optionally, the secondary particles have a D 50 0.7μm-2.0μm; Optionally, the compaction density of the positive electrode active material is 2.45 g / cm 3 -2.65g / cm 3 ; Optionally, the specific surface area of the positive electrode active material is 10 m 2 / g-13m 2 / g.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The positive electrode active material includes a substrate and a carbon coating layer coated on the surface of the substrate; Wherein, the matrix has a composition shown in Formula I: Li 1+a Fe b M c (PO4) d Formula I; Among them, -0.1≤a≤0.1, 0≤b≤1, 0≤c≤0.5, 0≤d≤1; M is at least one selected from La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al; Preferably, M is selected from Nb and further includes at least one of Al, Nb, W, Co, V and Ti.
6. A method for preparing a positive electrode active material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: A first mixed solution containing a first iron phosphate, a first lithium source, a first carbon source, and a first M source is prepared, and a first slurry is obtained by grinding, and a first precursor is obtained by a first spray drying process; A second mixed solution containing a second iron phosphate, a second lithium source, a second carbon source, and a second M source is prepared, and a second slurry is obtained by grinding, and a second precursor is obtained by a second spray drying process; The first precursor and the second precursor are mixed and sintered to obtain the positive electrode active material; the D of the first slurry 50 Less than the D of the second slurry 50 .
7. The preparation method according to claim 6, characterized in that: The D of the first slurry 50 With the second slurry D 50 The difference is greater than 0.2μm; Optionally, the particle size of the first iron phosphate is 80nm-200nm; the particle size of the second iron phosphate is 50nm-160nm; Optionally, the particle size D of the first precursor is 50 smaller than the particle size D of the second precursor 50 .
8. The preparation method according to claim 6, characterized in that: The D of the first slurry 50 0.25μm-0.45μm; Optionally, the D of the second slurry 50 It is 0.45μm-0.80μm.
9. The preparation method according to claim 6, characterized in that: The atomizer speeds of the first spray drying process and the second spray drying process are independently 30-50 Hz; Optionally, the particle size D of the first precursor and the second precursor is 50 Independently 15μm-45μm, water content ≤3.0%; Optionally, the first precursor and the second precursor are mixed in a mass ratio of (3:7)-(7:3); Optionally, the sintering temperature is 750° C.-850° C., and the sintering time is 6 h-12 h.
10. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 5 or the positive electrode active material prepared by the preparation method according to any one of claims 6 to 9.
11. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 10.
12. An electrical equipment, characterized in that: Comprising the battery of claim 11.
Citation Information
Cited By
Positive electrode active material and preparation method thereof, positive electrode plate and battery
CN121687948A
Positive electrode active material and preparation method therefor, positive electrode sheet, battery, and electric device
EP4779719A1
Positive electrode active material and preparation method therefor, positive electrode sheet, battery, and electric device
WO2026113097A1